P586 Comparative effectiveness of vedolizumab and ustekinumab as induction therapy in anti-TNF refractory Crohn's disease: a multi-centre retrospective cohort study. (25th January 2019) - Townsend, T; Razanskaite, V; Michail, S; Morgan, J; Davies, M; Storey, D; Watters, C; Penman, D; Swaminathan, M; Sabine, J; Chapman, A; Vyas, A; et al.
Abstract: Background: Anti-tumour necrosis factor (TNF) agents are effective in Crohn's disease (CD), but up to 30% of patients fail to respond or develop intolerance and require alternative biological therapy. Both vedolizumab and ustekinumab are licensed to treat anti-TNF refractory CD patients. Clinical trials of vedolizumab and ustekinumab in anti-TNF refractory patients suggest comparable efficacy, but no real-world data exist to guide clinicians' decision-making. 1, 2 We conducted a multi-centre retrospective cohort study to assess the comparative effectiveness of vedolizumab and ustekinumab in treating anti-TNF refractory CD. Methods: CD patients from four hospitals who were commenced on vedolizumab or ustekinumab following exposure to anti-TNF therapy were included. Disease activity was monitored serially by calculation of Harvey–Bradshaw index (HBI) for up to 4 months. Faecal calprotectin (FC) at baseline and subsequent visits were recorded if available. Clinical response was defined as a decrease in HBI ≥3 and remission by HBI <5. We compared the effectiveness of ustekinumab and vedolizumab. Results: After exclusion of patients without evaluable data, 51 patients commencing vedolizumab and 25 commencing ustekinumab therapy were included. Baseline characteristics (age, disease location, behaviour, smoking status and baseline FC) were comparable in both cohorts. Clinical response, remission and steroid-free remission rates were comparable between vedolizumab and ustekinumab at 2 and 4 months (Table 1). There was a significant reduction in HBI for vedolizumab at 2 months (1.8, 95% CI 0.50 to 3.13, p = 0.008) and ustekinumab at 4 months (3.4, 95% CI 1.84 to 4.96, p = 0.0001). Results at 2 and 4 months for vedolizumab and ustekinumab. Significance set at p = 0.05. Fisher exact test demonstrates no significant difference between treatments at 2 and 4 months. Conclusions: In a multi-centre cohort of anti-TNF refractory CD patients, vedolizumab and ustekinumab appear equally effective in the short-term. Our observations warrant longer-term follow-up and further validation in independent cohorts. References 1. Sands BE, Feagan BG, Rutgeerts P, et al. Effects of vedolizumab induction therapy for patient with Crohn's disease in whom tumour necrosis factor antagonist treatment failed. Gastroenterology 2014;147:618–627.e3 2. Feagan BG, Sandborn WJ, Gasink C, et al . Ustekinumab as induction and maintenance therapy for Crohn's disease. N Engl J Med 2016;375:1946–1960..